Comparative Study of Rectal Misoprostol to Oxytocin Infusion in Preventing Postpartum Haemorrhage After Caesarean Section - Adanikin, AI; Orji, E; Adanikin, PO; Olaniyan, O (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This comparative study aimed to compare the efficacy of rectal misoprostol to oxytocin infusion in preventing primary postpartum haemorrhage after caesarean section. Methods: Fifty pregnant women with identifiable risk factors for post-partum haemorrhage who delivered baby by caesarean section were randomized to receive 600 μg rectal misoprostol and a placebo infusion intravenously or placebo rectally and a 20 iu oxytocin infusion. Post-operative blood loss four hours after surgery was estimated by application of pads of known weight. Results: The mean immediate four hours post-operative blood loss was not significantly different between the rectal misoprostol and oxytocin infusion group (100.08 ± 24.85 ml versus 108.20 ± 29.93 ml; p =0.144) and the change between the pre-operative and post-operative hematocrit was similar. Conclusions: Post-caesarean section rectal misoprostol has comparative efficacy to oxytocin infusion in preventing post-partum haemorrhage. It is recommended for use as alternative uterotonic in settings where there is low refrigeration capacity. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 34-37 DOI: http://dx.doi.org/10.3126/njog.v8i2.9767